Development of an online-SPE-LC-MS method for the investigation of the intestinal absorption of 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PHIP) and its bacterial metabolite PHIP-M1 in a Caco-2 Transwell system. (1st January 2015) - Willenberg, Ina; von Elsner, Leonie; Steinberg, Pablo; Schebb, Nils Helge
Highlights: Development of an online-SPE-LC-MS method for PHIP, N -OH-PHIP, 4-OH-PHIP and PHIP-M1. Similar intestinal absorption of PHIP-M1 and PHIP in a Transwell system with a Caco-2 cell-monolayer. Bacterial metabolites could contribute to the toxicity of heterocyclic aromatic amines. Abstract: Heterocyclic aromatic amines such as PHIP are formed during the heat processing of food. PHIP undergoes bacterial metabolism leading to 7-hydroxy-5-methyl-3-phenyl-6, 7, 8, 9-tetrahydropyrido[3′, 2′:4, 5]imidazo[1, 2- a ]pyrimidin-5-ium chloride (PHIP-M1) as main metabolite. We developed an LC-MS method with automated sample preparation by online-solid-phase-extraction for the simultaneous quantification of PHIP and its mammalian and bacterial metabolites N -hydroxy-PHIP, 4-OH-PHIP and PHIP-M1 in biological samples. The method was used to investigate the transport of PHIP-M1 through a Caco-2 cell monolayer. The experiments show that PHIP-M1 rapidly crosses the cell monolayer and that PHIP-M1 is a substrate for P-glycoprotein and the multiple drug resistance 2 transporter. The intestinal absorption of PHIP-M1 is comparable with that of PHIP and a moderate to high bioavailability has to be expected. Thus, not only the human metabolites of PHIP but also the bacterial metabolite PHIP-M1 formed in the gut could contribute to the toxic effects of PhIP.